“Control Interno de Inventarios y su Incidencia en la Toma de Decisiones del Almacén Casa Pica Megaplastic del cantón La Maná Provincia de Cotopaxi Año 2019”. - Casa Arias, Elsa Violeta (2020)
The present research aims to analyze internal inventory control and its impact on decision-making at the Casa pica Megaplástic warehouse in La Mana canton. This investigation starts from the analysis of the problem related to an inadequate management of internal inventory control, which in some way affects the warehouse due to the loss of its products. To substantiate this study, sources of updated texts and documents referring to internal inventory control and decision-making were used. The methodology applied in this research is qualitative, descriptive, not experimental, the techniques used for the collection of information is through the interview and the survey with the COSO I internal control program. The results obtained show that there is a moderate internal inventory control as reflected in the survey, where the confidence level of the internal control system is 76.40%, while the risk level represents 23.60% considered as a moderate risk, in which the warehouse is already taking corrections. It is recommended to apply strategies in the internal control system such as the procedures manual so that it contributes to the improvement of the processes in a certain time.